MS Read: Context Sensitive Document Analysis in the WWW Environment - Milic-Frayling, Natasa; Sommerer, Ralph (2001)
Highly distributed environments like WWW pose challenges to the design and implementation of Information Management (IM) facilities. Authoring, data collection, indexing, searching, and document delivery on the Web appear completely disconnected. In particular, at the time a document is delivered from the hosting server as a result of search the search context is lost. Furthermore, user's queries typically provide an incomplete description of the information need. The focus of the search can also change considerably with the user’s exposure to the data. A prototype application called MS Read is presented which creates an evolving model of the user’s need during searching and browsing. It uses that model to analyze accessed documents. The model is based on the natural language processing of search queries and topic descriptions explicitly provided by the user while browsing though documents. It is semantically enhanced using linguistic and custom knowledge resources.